Experimental Views of Tran-Bend Particle Deposition in Turbulent Flow with Nanoscale Effect. (10th June 2018) - Zhou, Kun; Sun, Ke; Jiang, Xiao; Liu, Shaojie; He, Zhu; Ding, Zhou
Abstract : This paper presented experimental views of nano- and microaerosol distribution and deposition in turbulent tran-bend flows. These views included the particle flow measurement and particle depositions through individual bends, bifurcation bends, and those behind bends. Selected experiments were summarized and compared according to the gas flow, the bend geometry, and the particle flow properties. Based on recent studies, the influencing factors of environmental humidity, particle and surface properties, nanoparticle formation, coagulation, or evolution phenomena were discussed, and then research suggestions were given for future research and applications. It is specially mentioned that the new particle formation and nanoparticle growth affect its deposition under environmental contaminant conditions; nanoscale particle dynamics and transport have a growing trend on attracting the research and industry attentions.